Integrating Clinical and Translational Research Networks-Building Team Medicine - Salgia, Ravi; Kulkarni, Prakash (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
Medical centers are widely recognized as vital components of the healthcare system. However, academic medical centers are differentiated from their community counterparts by their mission, which typically focuses on clinical care, education, and research. Nonetheless, community clinics/hospitals fill a critical need and play a complementary role serving as the primary sites for health care in most communities. Furthermore, it is now increasingly recognized that in addition to physicians, physician-scientists, and other healthcare-related professionals, basic research scientists also contribute significantly to the emerging inter- and cross-disciplinary, team-oriented culture of translational science. Therefore, approaches that combine the knowledge, skills, experience, expertise, and visions of clinicians in academic medical centers and their affiliated community centers and hospitals, together with basic research scientists, are critical in shaping the emerging culture of translational research so that patients from the urban as well as suburban settings can avail the benefits of the latest developments in science and medicine. 'Integrating Clinical and Translational Research Networks-Building Team Medicine' is an embodiment of this ethos at the City of Hope National Medical Center in Duarte, California. It includes a series of papers authored by teams of leading clinicians, basic research scientists, and translational researchers. The authors discuss how engaging and collaborating with community-based practices, where the majority of older patients with cancer receive their care, can ensure that these patients receive the highest-quality, evidence-based care. Based on our collective experience at City of Hope, we would like to stress that the success of academic-community collaborative programs not only depends on the goodwill and vision of the participants but also on the medical administration, academic leadership, and policymakers who define the principles and rules by which cooperation within the health care industry occurs. We trust that our experience embodied in this singular compendium will serve as a 'Rosetta Stone' for other institutions and practitioners.